2018
DOI: 10.1111/jcmm.13818
|View full text |Cite
|
Sign up to set email alerts
|

LINC01287 regulates tumorigenesis and invasion via miR‐298/MYB in hepatocellular carcinoma

Abstract: Recently, it was reported that long non‐coding RNAs (lncRNAs) participated in promoting hepatocellular carcinoma (HCC) initiation and progression. Herein, we reported that the expression level of LINC01287 was elevated in HCC cell lines and tissues. LINC01287 down‐regulation inhibited HCC cells growth and invasion both in vitro and in vivo. LINC01287 exerted as a ceRNA and negatively regulated miR‐298 expression. MYB was identified as a downstream target of miR‐298. The miR‐298/MYB axis mediated LINC01287's ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…In addition, lncRNAs also act as “miRNA sponges” and sequester miRNAs to modify miRNAs target genes transcription, which has been identified as the lncRNA-miRNA-mRNA regulatory network in cancer tumorigenesis and progression [ 21 , 22 ]. For examples, LINC01287 regulates tumorigenesis of hepatocellular carcinoma via miR-298/MYB axis [ 23 ]. LncRNA SNHG15 promotes the proliferation and migration of lung cancer through targeting microRNA-211-3p [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lncRNAs also act as “miRNA sponges” and sequester miRNAs to modify miRNAs target genes transcription, which has been identified as the lncRNA-miRNA-mRNA regulatory network in cancer tumorigenesis and progression [ 21 , 22 ]. For examples, LINC01287 regulates tumorigenesis of hepatocellular carcinoma via miR-298/MYB axis [ 23 ]. LncRNA SNHG15 promotes the proliferation and migration of lung cancer through targeting microRNA-211-3p [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have recommended lncRNAs as vital regulators of gene expression and cancer development over the past few decades. From our previous studies, for example, we reported that LINC01287 and XIST could function as oncogenic lncRNA in human HCC [ 5 , 7 ]. LINC01419 was shown to promote tumor progression, this led to substandard prognosis in different types of cancers [ 8 – 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, researchers have identified a lncRNAs that are associated with HCC. Similarly, previous studies have reported that abnormal expression of lncRNAs contributes to HCC progression [5][6][7]. However, the underlying mechanisms have not been properly determined.…”
Section: Introductionmentioning
confidence: 95%
“…Hepatocellular carcinoma (HCC) is one of the common malignant tumors and remains the leading cause of cancer-related death worldwide 1,2. Multiple genes influence the tumorigenesis and progression of HCC and accumulation of multiple molecular changes are involved in the progression of HCC 3,4.…”
Section: Introductionmentioning
confidence: 99%